2013
DOI: 10.1128/iai.00059-13
|View full text |Cite
|
Sign up to set email alerts
|

The Fimbrial Protein FlfA from Gallibacterium anatis Is a Virulence Factor and Vaccine Candidate

Abstract: cThe Gram-negative bacterium Gallibacterium anatis is a major cause of salpingitis and peritonitis in egg-laying chickens, leading to decreased egg production worldwide. Widespread multidrug resistance largely prevents treatment of this organism using traditional antimicrobial agents, while antigenic diversity hampers disease prevention by classical vaccines. Thus, insight into its pathogenesis and knowledge about important virulence factors is urgently required. A key event during the colonization and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 48 publications
(44 reference statements)
2
50
0
1
Order By: Relevance
“…The results from these preliminary in vivo immunization trials indicated that at least GtxA-N, FlfA and Gab_1309 are promising vaccine candidates with a good protective potential. These results correspond well with previous results demonstrating the in vivo protective potential of FlfA [24]. Further studies, including larger group sizes, different doses and repeated immunization, are needed to confirm the protective potential of the recombinant proteins.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The results from these preliminary in vivo immunization trials indicated that at least GtxA-N, FlfA and Gab_1309 are promising vaccine candidates with a good protective potential. These results correspond well with previous results demonstrating the in vivo protective potential of FlfA [24]. Further studies, including larger group sizes, different doses and repeated immunization, are needed to confirm the protective potential of the recombinant proteins.…”
Section: Discussionsupporting
confidence: 81%
“…By implementing different in silico approaches and in vitro assays, we screened the Gallibacterium panproteome, resulting in a final selection of five proteins with a high predicted potential as vaccine candidates. Importantly, preliminary in vitro immunization results indicate protective potential of at least three of these candidates including FlfA, which has previously been tested and confirmed highly protective against homologous challenge in chickens [24]. Together, these results provide an important step in the development of a new and broadly protective vaccine against G. anatis.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations